2011
DOI: 10.3233/jvr-2011-0574
|View full text |Cite
|
Sign up to set email alerts
|

Workplace prejudice and discrimination toward individuals with mental illnesses

Abstract: Prejudice and discrimination represent a major barrier to the recovery and community integration of individuals with serious mental illnesses. Yet, little is known about the diverse ways prejudicial practices are enacted at the workplace beyond blatant discrimination. This paper presents findings about the manifestations of prejudice and discrimination at the workplace. Data were gathered from a national sample of individuals with serious mental illnesses who reported perceiving negative attitudes at work as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 39 publications
1
68
0
2
Order By: Relevance
“…), our results highlight how psychological problems represent the condition most frequently associated with a negative view (Russinovaa et al . ). With respect to first hypothesis, we underscore that people with SD were not evaluated most positively overall and that indeed, no differences emerged for intellectual disability and SD.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…), our results highlight how psychological problems represent the condition most frequently associated with a negative view (Russinovaa et al . ). With respect to first hypothesis, we underscore that people with SD were not evaluated most positively overall and that indeed, no differences emerged for intellectual disability and SD.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, Russinovaa et al . () found that employers tend to use more negative words (e.g. dangerous, unpredictable) when they describe individuals with mental illnesses than candidates presenting physical disability and were more concerned about their work and social performance.…”
Section: Introductionmentioning
confidence: 99%
“…Supervisors generally have major concerns about employing people with mental health problems [24][25][26], but prior experience seems to be an important factor in determining supervisors attitudes towards such employment [27]. Deepening their knowledge of mental health challenges has been found to be an effective strategy for winning supervisors cooperation [25,28].…”
Section: Introductionmentioning
confidence: 99%
“…To assess stigma in the workplace, questions were taken from the Workplace Stigma Survey, which is a 38-item self-report measure with four sections: “stigma and your work,” “stigma and your work environment,” “stigma and your recovery process,” and “your personal background” (Russinova, Griffin, Bloch, Wewiorski, & Rosoklija, 2011). Stigma at work was measured based on one’s perceived experience with stigma, and this was assessed in two ways.…”
Section: Methodsmentioning
confidence: 99%